Consequences of Nitric Oxide Metabolites in Leprosy: A Systematic Exploration - Kadam, Anita Dattatray; Khopade, Dipali Manoj; Kondaveeti, Suresh Bubu; Batra, Hitender Singh (International Journal of Pharmaceutical Investigation, 2025)
Background Leprosy, an ancient Disease remains a notable health concern in certain nations like India. It is an ongoing disease of infection brought on by Mycobacterium leprae. The production of Nitric Oxide by the action of inducible nitric oxide synthase serves as a crucial defense mechanism against bacterial activity, with its levels heightened in infectious diseases like leprosy. Nitric oxide exhibits potent antibacterial, antiviral and antitumor properties, yet it can be harmful to host cells, leading to tissue damage. Consequently, Nitrosative stress likely plays a pivotal role in leprosy progression. Objectives This being the case, the study's objective was to evaluate the state of nitric oxide generation and its deleterious effects on proteins and lipids in leprosy. 50 healthy controls, 16 Paucibacillary (PB) leprosy patients and 34 Multibacillary (MB) leprosy patients were enrolled. In comparison to healthy controls, leprosy patients had considerably greater levels of Nitric Oxide metabolites (NOx), the lipid peroxidation marker Malondialdehyde (MDA), nitrothiol and Protein Carbonyl (PC), an indication of protein oxidation. Leprosy patients' serum total thiol concentration, which functions as a defense against NOx, was significantly decreased in comparison to controls. Moreover, there was a noteworthy distinction observed between individuals with Paucibacillary leprosy and Multibacillary leprosy in terms of NOx, Nitrothiol, Malondialdehyde and Protein Carbonyl contents. Nitrothiol, Protein carbonyl and nitric oxide all showed positive correlations in the illness group, but nitric oxide, Protein carbonyl and Nitrothiol all showed negative correlations with Thiol. Thus, the elevation of Nitric Oxide metabolites (NOx) leads to structural changes in lipids and proteins, potentially contributing to leprosy progression.
Keywords: Leprosy; Malondialdehyde (MDA); Multibacillary (MB); Nitric Oxide metabolites (NOx); Nitrothiol; Paucibacillary (PB) Thiol; Protein Carbonyl (PC)